Do gourmet à gourmetização : a interface econômica e simbólica da gastronomia midiatizada - Arruda, Luzia da Silva (2019)
With the increase in income, consumption and aggressive marketing, which makes excessive use of labels, we have seen the phenomenon of Gourmetization, in which day to day foods started to have expensive versions of themselves. In this context, this thesis examines the forms of food mediatization, paying attention to advertisements, television programs, books, magazines and social media, in order to understand how the phenomenon of gourmetization interconnects food and other consumer sectors using gastronomic language. The choice of procedures is not dissociated from the theoretical-methodological trajectory of the studies of Culture, Communication and Consumption and through interdisciplinary orientations, dialogues with historical and other more specific context, but not less important, concepts such as those related to food, culture, communication and consumption. Thus, the idea is to think about the phenomenon of gourmetization in a sociological and communicational bias inherent in urban life in contemporary society, precisely because this gourmet wave is not alone, it is part of this whole social context. Gourmet discourse, with a glamorizing and consumerist bias as a market phenomenon, can be broad enough to become global but not homogenizing, because in discourse the symbolic uses are quite varied. It can be concluded that the concept of gourmet, born under the sign of pleasure, enjoyment without commitment, today has to handle socio-political and environmental demands. Food has become a field of moral and political values, through the double individual movement of personal choice and publicity, both private and public. Thus, the gourmet discourse, with its economic and symbolic interface, with social interactions and conflicts, enabled new ways of building public opinion, with new forms of citizenship and even politics. We insert food into a broader background in which culture deals with the relations of meaning that organizes social life and the relations of meanings, submitted to the socioeconomic, political and cultural movements that influence people's daily lives.